The Ambidextrous Pictet–Spengler Reaction: Access to the (+)- or (–)-Enantiomers of the Bioactive C-19 Methyl-Substituted Sarpagine/Macroline/Ajmaline Alkaloids from Either d- or l-Tryptophan - Rahman, M. Toufiqur; Cook, James M. (Synthesis, 2019)
Depicted in the following is the proof of concept, which is important to illustrate the full potential of the ambidextrous Pictet–Spengler (P-S) reaction. Previously, both d-tryptophan and l-tryptophan were employed to synthesize the key intermediates toward the natural enantiomers of C-19 methyl-substituted alkaloids. Now the enantiomeric series of the same key intermediates could also be synthesized from both d- or l-tryptophan in high yield and optical purity via this P-S/Dieckmann protocol. One can make either the natural or the unnatural alkaloids from either of the chiral starting amino acid esters, stereo- and enantiospecifically for biological screening.
Keywords: asymmetric Pictet–Spengler reaction; bioactive alkaloids; unnatural enantiomers; indole alkaloids; tetrahydro-β-carboline; bicyclo[3.3.1] framework